PREVENTIVE MAINTENANCE IN THE COLD SAW AREA AT PT. KBK - Hidayat, Rahmat; Rosyadi, Imron; Pinem, Mekro Permana; Sudrajad, Agung; Saefuloh, Iman; Erwin, Erwin (Trends in Mechanical Engineering Research, 2024)
In an increasingly competitive industrial environment, effective maintenance strategies are critical to ensure optimal machine performance and minimize downtime. This report focuses on the implementation of preventive maintenance in the cold saw area at PT. KBK, a steel production company. Preventive maintenance procedures were carried out to sustain machine reliability, particularly focusing on components such as the roll table, bolt coupling motor translation, sliding rails, and hydraulic motors. The report outlines the preventive maintenance schedule, inspection processes, and key findings during the maintenance period. The most frequently encountered issue was the deterioration of the saw blade, affecting cutting quality and operational efficiency. Contributing factors to these issues include human error, material hardness, improper maintenance methods, and machine age. A fishbone diagram analysis was used to determine root causes of failures, highlighting areas for improvement in maintenance practices. The study concludes that consistent preventive maintenance is essential to reduce machine failures, enhance productivity, and improve product quality. Recommendations are provided to enhance the maintenance process, including increased use of personal protective equipment (PPE) and more stringent inspection protocols.